Closed for Company Meetings: Between September 18 (5pm PDT) and September 22 (12pm PDT), Support and Sales requests *will be delayed*. Only time-sensitive issues will be addressed during that time. Thanks for your patience.

Nov 20 2011 | 11:52 pm

There are two posts discussing the formula for the scale object, but none really answer the question posted.

If the formula from the reference is:
y = b e-a log c ex log c

Where:
y = result
x = number to scale
a,b,c = the "three typed in arguments"
e = base of the natural log

My question:
There are 4 mandatory arguments, 5 with exponential scaling (which is why I'm interested in the formula). Given only three (a,b,c) - how does this work?

Also, what are the operators in the formula? I'm guessing:
y = b * (e-a) * log(c) * ln(x) * log(c)

Anyone dug in deep enough into their own scaling object?